SSW test in school children aged between 7 and 10 from two dissimilar socioeconomic cultural backgrounds - Becker, Karine Thaís; Costa, Maristela Julio; Lessa, Alexandre Hundertmarck; Rossi, Angela Garcia (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Hearing comprises a lot more than just a peripheral sensitivity. To interpret such sounds, the participation of wide-ranging hearing abilities is necessary. It is known that a motivating environment plays a key role to develop these abilities.Objective: study the hearing abilities evaluated by the Staggered Spondaic Word test - SSW - in school children aged between 7 and 10 from dissimilar socioeconomic and cultural backgrounds.Method: A prospective, clinical and watching study. 51 children participated in this study and were divided into two groups in accordance with their socioeconomic and cultural backgrounds. Accordingly, Group 1–G1 - (medium-high class) was comprised of 23 children and Group 2–G2–(medium-low class) had 28 children. SSW test was performed by analyzing both quantitative features: competitive right (CR) and competitive left (CL) conditions and the total of right answers in the test, and qualitative features: order effect (OE), hearing effect (HE), inversions and A-type standard.Results: Quantitative features: a statistically significant difference was found between the studied groups regarding the total of right answers in the test, but not in relation to CR and CL. Qualitative features: a statistically significant difference was noticed for the OE only. Although the statistical analysis has not found a significant difference for all the studied variants, it was possible to observe that G1 had higher results for all of them.Conclusion: the hearing abilities evaluated by the SSW test in school children aged between 7 and 10 showed higher scores in children with a medium-high socioeconomic and cultural backgrounds in comparison with those of medium-low socioeconomic and cultural backgrounds.
Keywords: hearing; socioeconomic factors; child